Some Selected Experimental Study on the Geotechnical Characteristics of Malaysian Laterite Soil Mixed with Sodium Carbonate (Na2CO3) - To Amiri, Shin; Dehghanbanadaki, Ali; Ayob, Mohamad (International Journal of Engineering and Technology, 2019)
This paper presents the results of an experimental analysis on the geotechnical characteristics of laterite soil found in Malaysia that is polluted with sodium carbonate at varying percentages ranging from 0% to 20%. In demonstrating the effects posed by the chemical reactions on the laterite soil in terms of its geotechnical properties, a selection of experimental tests was designed and conducted of which results indicated shear strength improvement of the soil. Apart from that, the permeability coefficient of the soil mixed with sodium carbonate was also measured using a falling head hydraulic conductivity test which was conducted on three different measurement timeframes namely immediate, one week, and after two weeks. The results indicated that when the percentage of chemical is increased, the permeability of the soil lessened in comparison to its natural properties. Additionally, the Atterberg limits gave out results which clearly indicated that a surplus percentage of sodium carbonate had been used to enhance the liquid and plastic limits in comparison to the limits in pure soil. Consequently, the pH value of the soil was altered from being acidic to being alkalineÂ Â